WHICH PRUDENCE AND ESG DISCLOSURE BETTER REFLECT PERFORMANCE? A REVIEW OF STAKEHOLDER AND AGENCY THEORIES - Putra, Arif Yoneffi; Fambudi, Imam Nurcahyo (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2024)
This study aims to test and analyze the effect of Prudence and Disclosure of Environmental, Social and Governance Information on Accrual Quality of companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Independent variables in this study are prudence and Disclosure of Environmental, Social and Governance Information while the dependent variable is Accrual Quality with Leverage, Firm Size and Crash Risk as control variables. This study uses a sample of 332 companies listed on the Indonesia Stock Exchange. The analysis model used is multiple regression analysis. This research is expected to be able to provide information about the factors that affect the accrual quality of a financial reporting to be considered by investors in making decisions. The results of this study indicate that Prudence and Disclosure of Environmental, Social and Governance Information have a positive and significant influence on Accrual Quality.Keywords: Prudence, Disclosure of Environmental, Social and Governance (ESG) Information, Accrual Quality